Multiple administrations of fluconazole increase plasma exposure to ruxolitinib in healthy adult subjects - Aslanis, Vassilios; Umehara, Kenichi; Huth, Felix; Ouatas, Taoufik; Bharathy, Savita; Butler, Andrew Avigdor; Zhou, Wen; Gadbaw, Brian (Cancer chemotherapy and pharmacology, 2019)
Purpose Ruxolitinib is metabolized by cytochrome P450 (CYP)3A4 and CYP2C9. Dual inhibitors of these enzymes (like fluconazole) lead to increased ruxolitinib exposure relative to a single pathway inhibition of CYP3A4 or CYP2C9. The magnitude of this interaction, previously assessed via physiologically based pharmacokinetic (PBPK) models, was confirmed in an open-label, phase 1 study in healthy subjects. Methods The effect of multiple doses (200 mg) of fluconazole on single-dose (10 mg) PK of ruxolitinib was investigated including evaluation of the safety and tolerability. The PK parameters of ruxolitinib alone (reference) were compared to those of ruxolitinib combined with fluconazole (test). The point estimate and corresponding two-sided 90% confidence interval for the difference between means of test and reference parameters were determined. Results All enrolled subjects ( N = 15) completed the study. When coadministered with fluconazole, geometric means of ruxolitinib PK parameters C max , AUC last , and AUC inf increased by 47%, 234%, and 232%, respectively, vs ruxolitinib alone. The median T max decreased slightly, apparent clearance decreased approximately threefold, and elimination half-life increased approximately 2.5-fold, upon ruxolitinib administration with fluconazole vs ruxolitinib alone. These results were consistent with the prospective predictions from a SimCYP PBPK model. Adverse events (AEs) were reported in six subjects (none were suspected to be related to ruxolitinib); no death or on-treatment serious AE was reported. Conclusions Coadministration of ruxolitinib with fluconazole significantly increased ruxolitinib systemic exposure; however, no AEs were attributed to ruxolitinib. Concomitant use of ruxolitinib with fluconazole (dose ≤ 200 mg) may require dose reduction/modification of ruxolitinib.